Neoproterozoic crustal growth and differentiation : Example of the Mayo Kebbi massif in southwestern Chad - (:unkn) unknown (My University, 2011)
The Mayo Kebbi massif (south-western Chad) is located between the Congo craton, the West African craton and the Saharan Metacraton. It consists of two greenstone belts (Zalbi and Goueygoudoum), three magmatic complexes (Gauthiot falls, Lere, Figuil) and post-tectonic intrusions distinguished on the basis of their structural, petrological, geochemical and geochronological characteristics. The geodynamic evolution of this massif includes the following phases:Phase 1: Emplacement of a Mafic to Intermediate Plutonic (MIP) complex. Boloro metadiorite, which belongs to this complex, is dated at 748 ± 4 Ma (U-Pb zircon age). This metadiorite is enriched in REE and characterized by LaN/YbN ~ 12, Sr/Y > 32, high LILE, Cr and Ni contents but negative anomalies in Nb-Ta. These features are attributed to partial melting of the slab followed by interaction of the produced magmas with the mantle wedge during their ascent.Phase 2: Emplacement of metagabbros and metabasalts (700 ± 10 Ma: U-Pb zircon age) of the Zalbi metavolcanic-sedimentary group. These rocks are characterized by a decoupling of LILE and HFSE, negative Nb-Ta anomalies, weak to moderate LREE fractionation relative to HREE. In particular, their geochemical characteristics are similar to modern back-arc basins. The isotopic compositions of Sr and Nd of these rocks preclude contamination by old continental crust of the related magmas during their emplacement. Accordingly, the MIP complex and the Zalbi metavolcanic-sedimentary group are associated to juvenile accretion in an island arc/back-arc basin tectonic setting.Phase 3: The syntectonic quartz metadiorite of Gauthiot Falls magmatic complex (665 ± 1 Ma: U-Pb zircon age, Penaye et al., 2006) is emplaced during a first collision event, which involves the Mayo Kebbi massif and the Adamaoua-Yade domain to the east. This event marks the beginning of the closure of the Zalbi back-arc basin and crustal thickening.Phase 4: The thickening is responsi
Keywords: African Research